The Leadership of Personnel Management in Islamic Education: Emerging Insights from an Indonesian University - Firman Mansir (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
Leadership is one of crucial things in an education management. It also happens in Islamic higher education institutions, especially in the case of its personnel management. This study aims to describe the leadership style in a personnel management of an Islamic higher education institution in Yogyakarta, Indonesia. This study belongs to qualitative research by using interview and observation in collecting the data. The obtained data then validated by triangulation and descriptively analyzed to produce relevant interpretation of the data. This research comes into a conclusion that the education success is not only measured from the class management, curriculum, students and so on, but also its personnel management. This study promotes that leadership in personnel management of Islamic higher Education needs good leadership style which based on the principle of siddiq, amanah, tabligh, and fathonah. It can be applied through recruitment, development, promotion and transfer, dismissal, compensation, as well as evaluation of employee performance